CRIMINAL POLICY FOR JUVENILE CRIMES FOR THE PERSPECTIVE OF INTERNATIONAL CRIMINAL LAW - Dr.Ameel Jabbar Ashour , Dr.Mohammed Salman Mahmood (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study deals with restorative justice as a modern approach to dealing with juvenile issues, as the correctional justice theory is the umbrella that provides all aspects of justice for children with the aim of achieving their interests in all situations that they may encounter. This study also seeks, through the descriptive, analytical and comparative approach, to study the concept of restorative justice for juveniles through the juvenile justice system in accordance with international and local laws, in addition to the practical framework for the application of restorative justice represented in the three levels represented by the "preventive" level, the remedial level, restorative justice. " And the level of aftercare and the importance of this study appears in that it helps to analyze the reality of the situation of juveniles in international and local legislation on the one hand, and practical practices towards juveniles through justice systems on the other hand, in order to reach that restorative justice is a complement to the juvenile justice system and not a substitute for it Where this study aimed to shed light on the concepts of restorative justice and their importance, and to indicate their levels by showing the ways of their work in the field of juvenile justice.